Facial Blood Flow Responses to Dynamic Exercise - Hayashi, Naoyuki; Kashima, Hideaki; Ikemura, Tsukasa (International Journal of Sports Medicine, 2020)
We reported previously that a static handgrip exercise evoked regional differences in the facial blood flow. The present study examined whether regional differences in facial blood flow are also evoked during dynamic exercise. Facial blood flow was measured by laser speckle flowgraphy during 15 min of cycling exercise at heart rates of 120 bpm, 140 bpm and 160 bpm in 12 subjects. The facial vascular conductance index was calculated from the blood flow and mean arterial pressure. The regional blood flow and conductance index values were determined in the forehead, eyelid, nose, cheek, ear and lip. One-way ANOVA and Tukey’s post-hoc test were used to examine effects of exercise intensity and target regions. The blood flow and conductance index in skin areas increased significantly with the exercise intensity. The blood flow and conductance index in the lip increased significantly at 120 bpm and 140 bpm compared to the control, while the values in the lip at 160 bpm did not change from the control values. These results suggest that the blood flow in facial skin areas, not in the lip, responds similarly to dynamic exercise, in contrast to the responses to static exercise.
Keywords: facial skin circulation; regional difference; temperature